Development of remote learning system in higher educational institutions of the Russian Federation: from local practice to integration into the digital university model. (9th June 2022) - Alexandrova, Tatyana; Bulgakova, Irina; Popov, Viktor; Gorodilov, Mikhail; Vertakova, Yulia
The experience of remote learning during the pandemic COVID-19 significantly accelerated the process of digitalisation of the higher education in Russia and intensified preparations for the transition to a model of the Digital University. However, even those educational institutions that successfully applied remote technologies in the educational process faced the problem of effectively managing the entire remote learning system. The aim of the study is to identify the management potential of remote learning at universities in Russia from the point of view of the methodology of active management systems. Models of the remote learning system in institutions of higher education relevant for different stages of development have been created; recommendations are made to integrate the proposed models into the Digital University model. Research results contribute to the development of the theory and practice of active management systems in terms of modelling remote learning in institutions of higher education.